Regulatory impediments to the private industrial sector development in Asia : a comparative study - Khatkhate, Deena R. (World Bank WashingtonUS, 1992)
Focuses on the domestic regulatory apparatus in five Asian countries: India, Indonesia, the Phillipines, Sri Lanka and Bangladesh in order to critically examine how it has affected the growth of private industrial sector development. Looks at industrial licensing and price control.